Analisis faktor aktivitas fisik, asupan makan, dan pengetahuan terhadap kejadian obesitas pada wanita dewasa di Kelurahan Kedaung - Radiansyah Badrani Nursalam; Ibnu Malkan Bakhrul Ilmi; Avliya Quratul Marjan (Poltekkes Kemenkes Aceh, 2025)
Background: Various factors can contribute to obesity, such as an unbalanced intake of carbohydrates, fats, and proteins, inadequate daily physical activity, and a lack of awareness about obesity.Objectives: Understanding the impact of physical activity factors, carbohydrate, fat, protein intake, and knowledge levels on the incidence of obesity in Kedaung Sub-District.Methods: This research employed a cross-sectional design with stratified random sampling to obtain the study sample. The study was conducted in the Kedaung area from September 6 to 9, 2024. The participants were adult women aged 21 to 49 years. The sample size, determined using the Lemeshow formula, comprised 46 respondents. Data collection was facilitated through a questionnaire distributed via Google Forms. The research was conducted within the Kelurahan Kedaung area. The data analysis methods used included univariate analysis with descriptive statistics and bivariate analysis with the chi-square test.Results: There is no significant association between physical activity (p score = 0,822), carbohydrate intake (p = 0,537), fat intake (p = 0,822), protein intake (p = 0,373), and knowledge level (p = 0,727) with the incidence of obesity in adult women in Kedaung sub district.Conclusions: All variables were tested and found to have no significant association with the incidence of obesity in adult women in Kelurahan Kedaung.